English Translations Of Quranic Verses Regarding Women: An In-Depth Analysis Of Loss And Gain In Meaning Based On Baker’S Taxonomy - Omar Ba Sharahil, Fatma Ahmed Abdallah (2022)
Studies have demonstrated that no translation of the Holy Quran is devoid of shortcomings; the point of interest is not whether there are shortcomings, but lies instead in the extent of the shortcomings, since translating the Holy Quran into a foreign language with perfect accuracy is an impossible task. Referring to several Quranic verses, claims have been made that Islam oppresses women and deprives them of their rights. This general perception that women are looked down upon, discriminated and insulted based on verses of the Holy Quran is common in the West, where translations of the Holy Quran are relied on. This thesis comprises an in-depth analysis of four English renditions of Quranic verses regarding women from the renditions by Pickthall, Arberry, Sarwar and Abdel Haleem. The selected verses are analysed with the aim of identifying the strategies used and determining the extent of loss or gain in meaning. Also, identification of the most dominant and least used strategies, and determining the themes demonstrating the most loss or gain in meaning. To this end, the verses regarding women were identified and categorised into five major themes based on their subject matter, then analysed using Baker’s taxonomy.